Pembelajaran Bahasa Arab Berbasis Fun Learning dengan Media Permainan Ular Tangga di MI Al-Muhtadin Arso VI - Nasita Dara; Husnul Khatimah; Laily Fitriani (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2022)
This study aims to describe learning Arabic based on fun learning with snakes and ladders game media. The research method used in this article is a case study method with a descriptive qualitative approach, where the researcher uses and obtains data from observations, interviews and documentation. The data analysis technique used in this research is the data analysis technique of the Miles and Huberman model which consists of three stages: data reduction, data presentation, and conclusion drawing. The three main topics discussed in this research are: a. How to learn Arabic for the fifth grade students of MI Al-Muhtadin Arso VI, b. How are the learning steps using snake and ladder media in learning Arabic for fifth grade students of MI Al-Muhtadin Arso VI, c. What are the advantages and disadvantages of using snake and ladder media in learning Arabic for fifth grade students of MI Al-Muhtadin Arso VI. The results of the study show that in learning Arabic using snakes and ladders media students play an active role in learning, because this media invites students to learn while playing. The learning process using the snake and ladder media was carried out by all students of class V MI Al-Muhtadin with 3 learning stages that had been prepared, namely introduction, core activity, and then closing. At the time of the introduction, the teacher opened the class with greetings, asked how things were and conveyed the scope of the material. At the core activity stage, the teacher gives mufrodat to students and continues with learning using snakes and ladders media. At the closing stage, the teacher asked again some of the meanings of mufrodat, appreciated students and closed the class. Abstrak Penelitian ini bertujuan untuk mendeskripsikan pembelajaran Bahasa Arab berbasis fun learning dengan media permainan ular tangga. Metode penelitian yang digunakan adalah metode studi kasus dengan pendekatan kualitatif deskriptif, di mana peneliti memperoleh data dari hasil observasi, wawancara dan dokumentasi. Teknik analisis data yang digunakan dalam penelitian ini adalah teknik analisis data model Miles dan Huberman yang terdiri dari tiga tahapan yakni: reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa dalam pembelajaran Bahasa Arab menggunakan media ular tangaa siswa berperan aktif dalam pembelajaran, karna media ini mengajak siswa untuk belajar sambil bermain. Proses pembelajaran menggunakan media ular tangga tersebut dilakukan oleh seluruh siswa-siswi kelas V MI Al-Muhtadin dengan 3 tahap pembelajaran yang sudah disusun yaitu pendahuluan, kegiatan inti, dan kemudian penutup. Pada saat pendahuluan disitu guru membuka kelas dengan salam, menanyakan kabar hingga menyampaikan cakupan materi. Pada tahap kegiatan inti guru memberika mufrodat pada siswa dan dilanjutkan dengan pembelajaran menggunakan media ular tangga. Pada tahap penutup guru menanyakan kembali beberapa arti mufrodat, mengapresiasi siswa hingga menutu kelas